Association of plasma remnant cholesterol with cognitive function in the middle-aged and elderly Chinese adults with type 2 diabetes: a cross-sectional study - Ren, Xiuwen; Zhang, Chengjun; Duan, Zhi; Zhao, Sen; Zhang, Zhihong; Zhang, Xueying; Sha, Yu; Ju, Lianyun; Mu, Jie; Gu, Yiyao; Gong, Yunyun; Yuan, Linhong; et al. (Frontiers in Nutrition, 2026)
BackgroundThe relationship between plasma remnant cholesterol (RC) level and cognitive function in middle-aged and older Chinese adults with type 2 diabetes (T2DM) was unclear.MethodsOne thousand eight hundred seventeen participants aged 55 to 75 were recruited from communities in Beijing. Demographic information and daily dietary intakes were collected by self-designed questionnaire. Fasting venous blood was obtained for quantitative analysis of plasma lipid parameters. The Montreal Cognitive Assessment (MoCA) was used to assess cognitive function. To explore the association between plasma RC and the risk of mild cognitive impairment (MCI), we performed logistic regression analysis and restricted cubic spline (RCS). Additionally, subgroup analyses were conducted to assess the influence of potential co-founders on the association.ResultsPlasma RC level was negatively correlated with daily intakes of vegetable, legume and fish intakes in patients with T2DM, and with daily intakes of cereals, vegetables, and legumes in non-T2DM subjects. Participants with plasma RC levels in the second (Q2), third (Q3), and fourth (Q4) quartiles had a higher risk for MCI compared to those in the first quartile (Q1) level of plasma RC, both in T2DM and non-T2DM participants. RCS results indicated a nonlinear relationship between plasma RC levels and the risk of MCI. Subgroup analysis showed that the association between plasma RC levels and the risk of MCI was pronounced in females and subjects aged 60 and above.ConclusionAn increase in plasma RC level is a potential risk factor for MCI. A plasma RC concentration below 0.578 mmol/L can decrease the risk of MCI in middle-aged and older individuals with T2DM. Similarly, a plasma RC concentration below 0.581 mmol/L may lower the risk of MCI in non-T2DM subjects. Consuming vegetables and legumes daily could help reduce the concentration of RC.